TRADITIONS: PAST THAT HAS BEEN TRANSITED, NARRATIVE AND REPETITION - M.Emir İLHAN (Fırat University, 2019)
In this article, tradition is taken as a transition of past, ‘past that has been transited’ is being traditionalized with the narrative activity that depends on the repetition between generations. The subject of past being transited, is taken as a ‘memory’ issue by various opinions is not explained sufficiently in terms of oral culture. However, instead, we can mention about traditionalizing by a ritualistic narrative that is based on impersonation. From this view point, past, no matter how it is being thought as a mere ‘memory’ concept, it contains a cause of “reminding”, can be seen as an attempt of narrative impersonating the past in order to transit to next generations. Traditionalizing the past with a narrative can be possible with repetition. Repetition, attempts the narratives that’s part of the oral culture such as folktale, ballad, epic, epos etc. impersonate ritualistically to re-temporal the past in the present and allows it to inherit as a heritage of the former generation. In summary narrative, draws out the past from being only a “memory” context and prevents the past being forgotten with re-experiencing a lively “performance”.